2013
DOI: 10.1353/jaas.2013.0019
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Race: Children and the Shifting Engagement with Racial/Ethnic Identity among Second-Generation Interracially Married Asian Americans

Abstract: Asian Americans have historically enjoyed one of the highest rates of intermarriage of any racial/ethnic group. By exploring the dynamics of interracial marriages among middle-class, professional Asian Americans in Chicago, this article examines what interracial marriages mean for these putative racial/ethnic “boundary crossers” and what they signify about assimilation, racial/ethnic identity, and redrawing of color boundaries in America. This article finds that for Asian Americans in this study, interracial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
4
18
0
Order By: Relevance
“…For some parents in our sample, inherent in the process of creating a multiracial family was negotiating racial differences with a White spouse. Similar to previous qualitative interviews of non-adopted Asian Americans with White spouses (S. H. Chang, 2015;K. H. Chong, 2013), there were parents who reported that their White spouses had limited awareness of racism and were uncomfortable in discussions of race.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For some parents in our sample, inherent in the process of creating a multiracial family was negotiating racial differences with a White spouse. Similar to previous qualitative interviews of non-adopted Asian Americans with White spouses (S. H. Chang, 2015;K. H. Chong, 2013), there were parents who reported that their White spouses had limited awareness of racism and were uncomfortable in discussions of race.…”
Section: Discussionsupporting
confidence: 62%
“…socialization of Asian-White youth (Atkin & Yoo, 2019), as existing studies focus on Asian-White adults (Brittian, Umaña-Taylor, & Derlan, 2013;V. Chong & Kuo, 2015) or are outside of developmental science (S. H. Chang, 2015;K. H. Chong, 2013).…”
mentioning
confidence: 99%
“…However, when we examine the findings of qualitative studies, what we learn about part Asian multiracial people is less conclusive. Qualitative research about non-Black multiracials reveals significant diversity in how such mixed people identify, and relate to, their White, Asian, and Latino ancestries, respectively (see Chang, 2016;Chong, 2013;Song, 2019;Standen, 1996;Vasquez, 2011), and there are still only a limited number of qualitative studies that have compared disparate types of multiracial experiences (see Tashiro 2016;Aspinall & Song, 2013;Strmic-Pawl, 2016).…”
Section: The Phenotypical and Experiential Diversity Of Multiracial Pmentioning
confidence: 99%
“…With regard to Asian Americans, who, like the Hispanics, occupy an “in-between” position in America’s traditional white-black racial divide, the initial debates had to do with what the surprisingly high rates of interracial marriage means for Asian Americans, and what this really indicates about their social assimilation and acceptance into American society. At the crux of this debate is the role of race for Asian Americans and their interracial marriage choices and family-making, with a number of recent studies showing that interracial marriages among Asian Americans may not be the indicator of assimilation as many would like to believe (Chong 2013; Olzak 1992; Song 2009). To complicate this debate further, the recent uptick in the rates of Asian interethnic marriages has intensified attention to the question of whether Asian Americans are really on the way to assimilation as viewed from a classic “straight-line” assimilation perspective (Gordon 1964), or whether it signifies something more complex about the social position of Asian Americans, their group identity, and path of assimilation.…”
Section: Asian Americans Intermarriage Assimilation and Racementioning
confidence: 99%
“…In relation to interracial marriages, a number of qualitative studies in recent years have helped shed light on the subjective dimensions of dating and spousal choices and romantic desires. These studies are valuable because they illuminate important sociological factors that inform individual choices from the perspective of the respondents (Chong 2013; Chow 2000; Fong and Yung 2000; Kibria 2002; Nemoto 2009). The articles by Colleen Fong and Judy Yung (2000) and Sue Chow (2000), focusing on Japanese and Chinese Americans in interracial marriages, were one of the first to bring attention to factors related to issues of racial and gender power relations in interracial marriages.…”
Section: Asian Americans Intermarriage Assimilation and Racementioning
confidence: 99%